Brains : how they seem to work - Purves, Dale (Upper Saddle River, New Jersey : FT Press Science, 2010)
One of the field's leading scientists takes readers on a guided tour through the recent history of neuroscience and offers a notion as to where neuroscience may well be headed next
1. Neuroscience circa 1960 -- 2. Neurobiology at Harvard -- 3. Biophysics at university college -- 4. Nerve cells versus brain systems -- 5. Neural development -- 6. Exploring brain systems -- 7. The visual system: Hubel and Wiesel redux -- 8. Visual perception -- 9. Perceiving color -- 10. The organization of perceptual qualities -- 10. Perceiving geometry -- 12. Perceiving motion -- 13. How brains seem to work
Includes bibliographical references (p. 235-280) and index
Keywords: Brain -- Popular works; Neurobiology -- Popular works